(untitled) (Indian Journal of Animal Production and Management, 2015)
A study on the constraints faced by adopted and non-adopted goat farmers in three rural villages of Assam viz. Nahira, Tepesia and Tetelia adopted by “All India Co-ordinated Research Project on Goat Improvement”, Goat Research Station, Assam Agricultural University, Byrnihut, Guwahati indicated that the major constraints perceived by the adopted and non-adopted goat farmers were inadequate grazing facility (38.10 and 28.57%), high cost of feeds (29.52 and 31.43%), lack of knowledge about scientific management of goats (0 and 39.05%), inadequate availability of breeding buck (0 and 30.48%), inadequate veterinary services (0 and 27.62%), lack of financial facility (45.71 and 65.71%), poor credit facility (29.52 and 31.43%), exploitation by middleman (40.95 and 52.38%) and predators attack (29.52 and 30.48%) respectively.